Molecular ecology of the fiddler crab Austruca perplexa (H. Milne Edwards, 1852): genetic divergence along a major biogeographical barrier, Wallace's Line. (7th December 2021) - Hardianto, Eko; Permata Wijayanti, Diah; Shy, Jhy-Yun; Mather, Peter; Hughes, Jane; Imai, Hideyuki
Abstract: Genetic diversity and population structure in the fiddler crab Austruca perplexa were investigated to acquire a better understanding of the evolutionary history of the species. Nucleotide sequence analysis was performed from a polymerase chain reaction-amplified fragment of the mitochondrial DNA control region. A 691 bp nucleotide sequence was obtained from 618 specimens collected from 13 sites across Japan, Taiwan, the Philippines, Indonesia and Australia. Haplotype diversity ranged from 0.8 to 0.99, and nucleotide diversity values were lower (range, 0.30–1.9%) than those reported previously for other crustacean taxa. Gene flow was evident within populations in Japan and western Indonesia, but absent among all other populations, including eastern Indonesia. This pattern conforms to the one observed in many other marine taxa across the major biogeographical region referred to as Wallacea. The population pairwise fixation index ( F ST ) and F ST P- values were high and significant among many sites, implying that gene flow is restricted among most of the geographical regions sampled here. We hypothesize that physical oceanic barriers coupled with a short pelagic larval duration are responsible for creating the patterns we found. Strong evidence for population structure in a species that has relatively high dispersal potential, resulting in among-population differentiation, is a potential driver of evolutionary novelty. Our results provide a foundation for developing better conservation strategies for this widespread intertidal species.